William Safire on language - Safire, William (New York Avon Bokks, 1981)
Written by a New York Times columnist renowned for his crotchety wit, this tome enlightens readers concerning proper usage, correct pronunciation, the roots of daily discourse, and the vacuous lingo in which "subsume" is co-opting "co-opt", word-burning stoves become "energy systems", and stores that sell eyeglasses squint out at the public as "vision centers". The author is aided in his campaign for precision and clarity in language by a legion of word buffs, language lovers, and learned eccentrics.
Keywords: English Language - Idioms, corrections, errors; English language - Usage